1998
DOI: 10.1016/s0896-6273(00)80484-5
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide as an Autocrine Regulator of Sodium Currents in Baroreceptor Neurons

Abstract: Arterial baroreceptors are mechanosensitive nerve endings in the aortic arch and carotid sinus that play a critical role in acute regulation of arterial blood pressure. A previous study has shown that nitric oxide (NO) or NO-related species suppress action potential discharge of baroreceptors. In the present study, we investigated the effects of NO on Na+ currents of isolated baroreceptor neurons in culture. Exogenous NO donors inhibited both tetrodotoxin (TTX) -sensitive and -insensitive Na+ currents. The inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
94
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(97 citation statements)
references
References 67 publications
2
94
1
Order By: Relevance
“…20,21 Indeed, the modulation of ion channels represents one of the important functional effects of NO. In the cardiac systems, NO can inactivate the cardiac ryanodine receptor Ca 2ϩ release channel 22 and plays an important role in cardiac pacemaking cells by mediating a muscarinic cholinergic attenuation of the L-type Ca 2ϩ current in mammalian sinoatrial and atrioventricular node.…”
Section: Effects Of No On Other Ion Channelsmentioning
confidence: 99%
“…20,21 Indeed, the modulation of ion channels represents one of the important functional effects of NO. In the cardiac systems, NO can inactivate the cardiac ryanodine receptor Ca 2ϩ release channel 22 and plays an important role in cardiac pacemaking cells by mediating a muscarinic cholinergic attenuation of the L-type Ca 2ϩ current in mammalian sinoatrial and atrioventricular node.…”
Section: Effects Of No On Other Ion Channelsmentioning
confidence: 99%
“…This gaseous molecule can spread, in fact, from its site of production and act in adjacent cells, either directly or through second messengers, on various protein substrates, including ion channels. Its influence on Ca 2ϩ -activated K ϩ channels (Bolotina et al, 1994), Na ϩ channels (Li et al, 1998), and Ca 2ϩ -activated Cl Ϫ currents (Waniishi et al, 1998) has been well documented, and several reports suggest that it is also involved in the modulation of high-voltage-activated (HVA) Ca 2ϩ channels [references in Carabelli et al (2002)]. In previous studies, we have found that NO donors and cGMP analogs significantly reduce the amplitude of macroscopic currents flowing through both L-and P/Q-type Ca 2ϩ channels in rat insulinoma RINm5F cells (Grassi et al, 1999a).…”
mentioning
confidence: 99%
“…The left kidney was exposed through a left flank incision, and the left RGA and CG were isolated from the connective tissue and excised for dissociation and cell culture as described previously. 11,12 The ganglia were incubated in the digestive medium for 55 minutes at 37°C. Enzymatic activity was terminated by a trypsin inhibitor.…”
mentioning
confidence: 99%